PENINGKATAN KEMAMPUAN MENULIS DI ERA DIGITAL PADA GURU DI DESA GUNUNG SARI - anisa nurul fitri; Fitriatun Nisa; Ikmal Awaludin; Rizki; Hasbi Ash Shiddieqy; Rusdiono (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2023)
This study aims to determine the capacity of teachers in Gunung Sari village in learning in the current digital era. The subject of this study is the teacher as an educator in Gunung Sari Village, Pamijahan District. To increase the ability and capacity in learning in the digital era, it is required to have literacy skills so that they can be taught to students. This research method uses a qualitative approach with collection in the form of observations and interviews. The results of the study show that there are still many teachers in Gunung Sari village who are not ready to face the digital revolution, especially in terms of increasing literacy in the current digital era, rapid developments in the digital world today make it difficult for teachers to align literacy strategies.